2018
DOI: 10.17219/acem/68967
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of tumor necrosis factor alpha inhibitors on methotrexate-induced pancreatic toxicity

Abstract: Background. Methotrexate (MTX), a folate antagonist, is commonly used in the treatment of many different types of cancer and inflammatory diseases, including pancreatic cancer, although its side effects on the pancreas have not yet been researched. The mechanism of MTX-induced toxicity is not well known, and it has been reported in high-dose toxicity studies that the pancreas is sensitive to toxic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…These side effects are thought to be the result of oxidative damage caused by reactive oxygen species. In addition, other toxic effects of MTX are neurotoxicity, pulmonary fibrosis, testicular toxicity, pancreatic toxicity and intestinal mucositis (Mercantepe et al, 2018). There are studies in the literature to prevent hepatotoxicity and nephrotoxicity, which are the most important side effects caused by MTX (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These side effects are thought to be the result of oxidative damage caused by reactive oxygen species. In addition, other toxic effects of MTX are neurotoxicity, pulmonary fibrosis, testicular toxicity, pancreatic toxicity and intestinal mucositis (Mercantepe et al, 2018). There are studies in the literature to prevent hepatotoxicity and nephrotoxicity, which are the most important side effects caused by MTX (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These side effects are thought to be the result of oxidative damage caused by reactive oxygen species. In addition, other toxic effects of MTX are neurotoxicity, pulmonary fibrosis, testicular toxicity, pancreatic toxicity and intestinal mucositis [32][33][34]. There are studies in the literature to prevent hepatotoxicity and nephrotoxicity, which are the most important side effects caused by MTX [16,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…10 Caspase-3 is a cysteine-protease group enzyme that plays an important role during apoptosis and is an important apoptotic marker. 36 Several studies have reported that the amount of caspase-3 in the organism increases significantly after irradiation. 37 Mercantepe et al (2019) suggested that IR activated caspase-3 in renal tubule cells and enhanced the amount of apoptosis.…”
Section: Vacuolization Of Tubular Epithelial Cellsmentioning
confidence: 99%